Elucidating a Complicated Enantioselective Metabolic Profile: A Study From Rats to Humans Using Optically Pure Doxazosin - Dezhi Kong; Yuan Tian; Yuan Tian; Kunfeng Duan; Wenyan Guo; Qingning Zhang; Panpan Zhang; Zuxiao Yang; Xia Qin; Leiming Ren; Wei Zhang (Frontiers Media S.A., 2022)
Doxazosin (DOX) is prescribed as a racemic drug for the clinical treatment of benign prostatic hyperplasia and hypertension. Recent studies found that the two enantiomers of DOX exhibit differences in blood concentration and pharmacological effects. However, the stereoselective metabolic characteristics and mechanisms for DOX are not yet clear. Herein, we identified 34 metabolites of DOX in rats based on our comprehensive and effective strategy. The relationship among the metabolites and the most discriminative metabolites between (−)-DOX and (+)-DOX administration was analyzed according to the kinetic parameters using state-of-the-art multivariate statistical methods. To elucidate the enantioselective metabolic profile in vivo and in vitro, we carefully investigated the metabolic characteristics of metabolites after optically pure isomers administration in rat plasma, rat liver microsomes (RLMs) or human liver microsomes (HLMs), and recombinant human cytochrome P450 (CYP) enzymes. As a result, the differences of these metabolites were found based on their exposure and elimination rate, and the metabolic profile of (±)-DOX was more similar to that of (+)-DOX. Though the metabolites identified in RLMs and HLMs were the same, the metabolic profiles of the metabolites from (−)-DOX and (+)-DOX were greatly different. Furthermore, four human CYP enzymes could catalyze DOX to produce metabolites, but their preferences seemed different. For example, CYP3A4 highly specifically and selectively catalyzed the formation of the specific metabolite (M22) from (−)-DOX. In conclusion, we established a comprehensive metabolic system using pure optical isomers from in vivo to in vitro, and the complicated enantioselectivity of the metabolites of DOX was clearly shown. More importantly, the comprehensive metabolic system is also suitable to investigate other chiral drugs.